2014
DOI: 10.1002/jbm.b.33351
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposited silk coatings for bone implants

Abstract: The aim of this study was to characterize the mechanical properties and drug elution features of silk protein-based electrodeposited dental implant coatings. Silk processing conditions were modified to obtain coatings with a range of mechanical properties on titanium studs. These coatings were assessed for adhesive strength and dissolution, with properties tuned using water vapor annealing or glycerol incorporation to modulate crystalline content. Coating reproducibility was demonstrated over a range of silk c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 48 publications
(133 reference statements)
0
24
0
Order By: Relevance
“…According to results reported in vivo, the combination of acid etching and sandblasting can accelerate bone regeneration 36) . Elia et al 37) reported that a higher adhesive strength was obtained on a rougher surface when the same concentration of silk fibroin was applied for a coating. Therefore, SLA substrates were used for surface coating by an electrogel in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to results reported in vivo, the combination of acid etching and sandblasting can accelerate bone regeneration 36) . Elia et al 37) reported that a higher adhesive strength was obtained on a rougher surface when the same concentration of silk fibroin was applied for a coating. Therefore, SLA substrates were used for surface coating by an electrogel in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The time for the completion of degradation mainly depends on the silk fibroin concentration and pore size inside the scaffolds. In Elia's study 37) , researchers explored drug release from an electrodeposited silk fibroin coating using FITC-dextrans. The drug release curve was in line with that observed in traditional systems.…”
Section: Discussionmentioning
confidence: 99%
“…185 Very recently, these gels were studied as potential coatings for bone implants. 186 To add an antibacterial activity, silk fibroins were chemically modified by tetracycline, a globally positively charged antibiotic. The obtained positively charged functionalized silk was deposited on a titanium cathode.…”
Section: Electrogelation Of Silkmentioning
confidence: 99%
“…More recently electrodeposition has been extended to silk fibroin protein‐based gels (termed e‐gels) and this method provides a means to prepare silk‐based materials for emerging medical applications . These studies report a reversible electrogelation of silk films at an anode surface with the low localized pH adjacent to the anode being important for the deposition mechanism .…”
Section: Self‐assembling Biopolymer Hydrogels As Integrative Materialsmentioning
confidence: 99%